Оценка эффективности внедрения социальных инноваций в деятельность санаторно-курортного комплекса (Путеводитель предпринимателя, 2020)
The need for the sanatorium complex development is analyzed, the social innovation implementation as a way of supporting is proposed, a classification of the effects produced by the social innovations application in the health centre activity is given, and a formula for assessment integrating is developed.